The Evaluation of Functional Education and Training Program Management of English Subject Teacher Competency Improvement in The Collaboration Pattern With Pemalang Regency Government and Center and PPPPTK Language Jakarta - Zulfikar, Anhar Hafidh; Sumaryanto Florentinus, Totok; Suminar, Tri (Educational Management, 2020)
The quality and the level of Human Resources (HR) hold a very strategic position in an organization. Besides, Human Resources also play an important role in the process of achieving the vision and the mission of an organization. Therefore, it is needed the existence of management consistently and continuously towards Human Resources itself. The purpose of this study is to find out and to analyse; 1) How the planning used in functional education and training program for improving English teacher competency in Pemalang Regency. 2) How the implementation functional education and training program for improving English teacher competency in Pemalang Regency, and 3) How the evaluation offunctional education and training program for improving English teacher competency in Pemalang Regency. This research used a descriptive method with a qualitative approach. The type of qualitative research approach used was case study. The data collection process was carried out byobservations, interviews, and document studies. The results of the study showed; 1) the implementation of functional education and training program for improving English teacher competency in Pemalang Regency included the process of analysing the needs, setting goal, training model, determining participant and presenter 2) the implementation of functional education and training program for improving English teacher used full face-to-face pattern of 60 Learning Hours. 3) the evaluation of functional education and traing program for improving English teacher competency showed the improvement of teacher competency which was indicated by the results of post-test at the end of the program. Suggestion for education and training providers is that the management of education and training program should be maximized, especially for the management of supportingfacilitie program, in this case is the provision of close worship place to the training room for timing efficiency.